Pharmacological Inhibition of Necroptosis Promotes Human Breast Cancer Cell Proliferation and Metastasis - Shen F (OncoTargets and Therapy, 2020)
Feng Shen,1,* Xiangou Pan,2,* Min Li,3,* Yixing Chen,2 Ying Jiang,3 Jian He2 1Department of Medical Oncology, Zhongshan Hospital, Fudan University, Shanghai 200032, People’s Republic of China; 2Department of Radiation Oncology, Zhongshan Hospital, Fudan University, Shanghai 200032, People’s Republic of China; 3Department of General Surgery, Zhongshan Hospital, Fudan University, Shanghai 200032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian HeDepartment of Radiation Oncology, Zhongshan Hospital, Fudan University, Shanghai 200032, People’s Republic of ChinaTel/ Fax +86-021- 64041990Email hejian62@163.comYing JiangDepartment of General Surgery, Zhongshan Hospital, Fudan University, Shanghai 200032, People’s Republic of ChinaTel/Fax +86-21-64041990Email jiang.ying3@zs-hospital.sh.cnBackground: Breast cancer remains a great threat to females worldwide. As a recently defined programmed cell death pathway that associates with immune activation, RIP1/RIP3/MLKL necroptosis signaling has been implicated in a variety of diseases. The present study aimed to investigate the role of RIP1/RIP3/MLKL signaling in breast cancer cell proliferation and metastasis in vivo and in vitro.Methods: Western blot and quantitative real-time PCR were performed to evaluate the activation of necroptosis signaling in clinical human breast cancer tissues. Correlation of necroptosis signaling markers with clinicopathological parameters was statistically assessed. Cell viability assay, colony formation assay, wound healing assay, and transwell migration and invasion assays were performed to investigate the effects of necroptosis inhibition on breast cancer cell proliferation and metastasis.Results: Clinical breast cancer tissues showed significantly higher levels of tumor necrosis factor alpha (TNFα), RIP1, RIP3 and MLKL at both mRNA and protein levels as compared with their paired non-cancerous tissues. Phosphorylation of RIP3 and MLKL was also remarkably provoked. Statistics showed that both RIP1 and MLKL positively correlated with cancer parameters such as N-cadherin (p=0.002 for RIP1 and p=0.021 for MLKL) and Ki67 (p=0.031 for RIP1 and p=0.05 for MLKL). The MLKL expression level significantly correlated with tumor size (p=0.001) and the proliferation indicator Ki67 (p=0.018). In addition, pharmacological inhibition of the necroptosis signaling using necrostatin-1 promoted breast cancer cell proliferation and colony formation by approximately 50%. Blockade of necroptosis signaling also accelerated wound healing process and cell transmigration in breast cancer cells.Conclusion: Our results suggested that pharmacological inhibition of necroptosis promoted breast cancer cell proliferation and metastasis. Modulation of tumor cell necroptosis might represent a novel strategy as to breast cancer treatment.Keywords: breast cancer, necroptosis, RIP1, MLKL, proliferation, metastasis